Challenges facing probation officers working with young persons in conflict with the law - Volsak, Nobubele (Rhodes University, Faculty of Humanities, Department of Social Work, 2001)
This study aimed at focusing on the challenges facing probation officers working with young persons in conflict with the law, in the Eastern region, which forms part of the Eastern Cape Province. The main purpose of the study was to explore the experiences of probation officers in terms of the legislation that they are using when making decisions pertaining to young persons and the types of programmes that they offer to young persons for diversion and prevention purposes. The researcher also wanted to generate a greater understanding of the resources which probation officers have and need in order to run their programmes successfully to young persons, as well as to explore their feelings about working with young persons. The researcher did some literature review in relation to this field, where it became evident that probation services in respect of young persons in conflict with the law, is a relatively new field of specialisation in South Africa. This field started around 1995 as a result of the Inter - Ministerial Committee (IMC) on young people at risk, which was set up to respond and manage the crisis of more than one thousand children who were released from prisons and police cells. The IMC then, identified probation officers as leading role players in dealing with young persons in conflict with the law. An exploratory (non - experimental) design was used to carry out the research. A qualitative research method was also used as it attempts to describe and explain social reality from the points of view of the participants. This is because the researcher was interested to find out the experiences of probation officers in relation to their work with young persons. A non - probability purposive sample of all (11) probation officers was used. A semi - structured interview schedule with both closed and open - ended questions was used to collect data. All the information gathered from those personal interviews, was analysed by hand because the researcher wanted to interpret and produce social explanations. The findings of this small - scale study have revealed that there are a number of challenges facing probation officers. For example presently there is no comprehensive legislation for the management of young persons caught up in the criminal justice system. Instead, limited provisions are spread throughout a number of separate statutes, which make it difficult for probation officers to apply them. This study has also revealed that there is a shortage of human and material resources, which somehow impact negatively on how probation officers render services to their clientele. All probation officers in this study have positive feelings and attitudes about their work despite the fact that there are some challenges facing them that need to be addressed. Specific recommendations have been made based on the findings of this study, which could contribute to the development of probation services in respect of young persons in conf lict with the law
Keywords: Probation officers; Probation officers -- Attitudes -- South Africa -- Eastern Cape; Juvenile delinquents; Probation